Brother bear. (Pasig City : Viva Video, 2004)
Disney proudly present Brother Bear, an epic animated adventure full of comedy and heart, with five great new songs from Academy award winner Phil collins, it's an entertainment experience the whole family will enjoy. In this spectacular coming-of-age story based on ancient myths, an impulsive boy named Kenai is magically transformed into a bear. He has no choice but to see the world through another's eyes while he learns some valuable life lessons and strives to regain his human form. Unable to communicate with his human form. Unable to communicate with his human brother, Kenai teams up with Koda, an irrepressible bear cub, and sets out on a courageous journey of self-discovery. Amidst breathing, beautifully animated scenery, they encounter a forest full of wildlife, including hilarious moose brothers Rutt and Tuke, woolly mammoths, rambunctious rams and more! BROTHER BEAR is an unforgettable tale that explores the true meaning of brotherhood and what it means to walk in the footstep of another.